White-dwarf equation of state and structure: the effect of temperature. (6th November 2017) - Fantoni, Riccardo
Abstract: We study the effect of having a finite temperature on the equation of state and structure of a white dwarf. In order to keep the treatment as general as possible we carry out our discussion for ideal quantum gases obeying both the Fermi–Dirac and the Bose–Einstein statistics even though we only use the results for the free electron gas inside a white dwarf. We discuss the effect of temperature on the stability of the star and on the Fermi hole.